Variations in rhizosphere soil total phosphorus and bioavailable phosphorus with respect to the stand age in Pinus massoniana Lamb. - Xu, Yaowen; Ge, Xiaogai; Zhou, Benzhi; Lei, Lei; Xiao, Wenfa (Frontiers in Plant Science, 2022)
Phosphorus (P) is nutrient limiting plant growth in subtropical regions. However, our understanding of how soil P responds to an increase in stand age is rather poor. In particular, little is known about how bioavailable P pools (soluble P, exchangeable P, hydrolyzable P, and ligand P) shift with change in stand age. Moreover, the P cycle in rhizosphere soil has the most direct and significant influence on plants. The aim of the present study was to determine the concentrations of total P in various rhizosphere soil bioavailable P fractions in 5-, 9-, 19-, 29-, and 35-year-old stands of Pinus massoniana Lamb. According to the results, total P (TP) concentration and N:P ratio in rhizosphere soil first decreased, and then increased with an increase in stand age. Soluble P concentration decreased first, and then increased with an increase in stand age; exchangeable P and ligand P decreased in the early stage and tended to be stable in the middle and late stages; whereas hydrolyzable P increased first, and then decreased. Structural Equation Model results suggested that ligand P and soluble P were the major factor affecting the TP. In addition, soil microorganisms and acid phosphatase-driven hydrolyzable P play a crucial role in soil bioavailable P cycling. Overall, the results of our study provides a mechanistic understanding of soil bioavailable P cycling under low available P conditions, and a basis for an effective P management strategy for the sustainable development of P. massoniana plantations.